Diversity and Distribution of Endomycorrhizae and Dark Septate Endophytes of some Economically Important Bamboos of Assam, India - Vipin PARKASH; Liza HANDIQUE; Priya DHUNGANA (Notulae Scientia Biologicae, 2019)
The genus Bambusa Schreb. which belongs to the Poaceae family is commonly present in north-eastern region of India. A survey was undertaken in three villages viz. Tilikiaam, Maoutgaon and Nathgaon of Jorhat district, Assam, North-east India, where natural populations of Bambusa species were observed. Four bamboo species i.e. Bambusa bambos (L.) Voss, B. tulda Roxb., B. pallida Munro and B. nutans Wall. ex. Munro were found locally economically important and the rhizospheric soil and root samples were collected for  screening of dark septate endophytes (DSE) as well as arbuscular mycorrhizal (AM) colonization. Quantitative analysis of root samples showed the presences of all the three types of endomycorrhizal root infection/colonization namely hyphal, vesicular and arbuscular. Beside this, the dark septate endophytic infections were also observed in all the bamboo species. The cent-percent endomycorrhizal (hyphal and vesicular) and DSE hyphal infections were reported in roots of all the bamboo species respectively. There were variations observed in arbuscular infection in B. nutans and B. bambos (100%), B. pallida (90%) and least in B. tulda (70%). Qualitative analysis revealed that the Endomycorrhizae found in the rhizospheric soil predominantly belongs to five genera viz. Glomus, Acaulospora, Gigaspora, Scutellospora and Entrophospora. The genus Glomus, is the most dominant, with 17 species (61%), Acaulospora with 7 species (25%), Entrophospora with 2 species (7%), Scutellospora (3.5%) and Gigaspora (3.5%) with 1 species each. Distribution of AM fungi were highest in B. bamboos (67.7%) followed by B. pallida (19.4%), B. tulda (11.1%) and least in B. nutans (2.8%). Bamboo resources have been considerably declining due to exploitation, shifting cultivation, gregarious flowering and extensive forest fires from the natural habitats. Therefore, further microbial based applied researches should be undertaken to protect the dwindling natural bamboo resources and considering AMF bioinoculants in future management practices in order to maintain diminishing ecosystems.